SOCIAL ENGAGEMENT STRATEGY OF ENGLISH LANGUAGE LEARNERS FOR ENHANCING GRAMMAR - Yunita, Wisma; Hati, Gita Mutiara; Arono, Arono; Baker, John R.; Abdullah, Irwan (LLT Journal: A Journal on Language and Language Teaching, 2025)
Language learning, including grammar learning, requires social strategies involving interaction. The study explored the prevalence of social strategy use, patterns of social strategy use employed by English Language Learners (ELL) in learning English grammar, and the rationale behind their use. Using purposive sampling and a mixed-methods design (Grammar Learning Strategies Inventory – GLSI – and follow-up semi-structured interviews) with 194 Indonesian undergraduate respondents showed that social strategies were most employed, followed by metacognitive, cognitive, and affective. The findings also illustrated three social strategy use patterns: (a) involving teachers and more proficient others, (b) practicing with peers, and (c) involving peers as motivators. The rationales for social strategy use were further demonstrated: (a) to understand and avoid mistakes in the use of grammar, (b) share and enhance understanding of grammar materials, (c) know errors and correct them to participate more in learning, and (d) improve grammar usage. These findings provide practical and theoretical insights into students' social strategy use in the ELL context. Limitations and opportunities for additional research are also presented.